PENGEMBANGAN INSTRUMEN EVALUASI BERBASIS KEMAMPUAN PEMECAHAN MASALAH PADA MATERI EKSPONEN DI TINGKAT SMA - Rosyadi, M.; Yuhana, Yuyu (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
The purpose of this research is to produce a test instrument to measure mathematical problem-solving ability by looking at the development procedures and the quality of the mathematics problem solving instruments developed. The research used is the type of research (R&D) that is the development of test instruments to measure the ability to solve mathematical problems. The development model of this research instrument is developed on the basis of the Tessmer model which is the formative type of evaluation, i.e. (1) preliminary stage, (2) self evaluation stage, (3) prototyping stage (expert reviews, one-to-one and small group) and (4) field test stage. The test subject of the experiment were X Students of SMAN 2 Bayah which amounted to 25 students. Based on the results of experiments conducted, it is found that: (1) math problem solving test instrument has been said "valid" because based on the CVR results are 1 and meet the criteria of  ≥ 0.99 and CVI is 1 with a category perfectly suitable or in the range 0,68-1,00 (2) mathematical problem-solving test instrument is said to be reliable with a value of 0.754 with high category, and is in the range of 0.60 < r11 < 0,80 (3)instrumen test the math problem solving device has a level of difficulty good then the average level of difficulty obtained is 0.58 with the medium category that is in the range of 0.31 to 0.70. (4) instrumen test math problem solving devices has a power a good differentiator and the average distinguishing power obtained is 0.35 with sufficient category or is in the range Dp > 0.2. As a result, the produced instrument is appropriate for assessing pupils' mathematical problem-solving abilities